Estrogen carcinogenesis in the hamster kidney: role of cytotoxicity and cell proliferation. - Li, J J (1993)
Both natural and synthetic estrogens are capable of inducing renal neoplasms in Syrian hamsters with an incidence approaching 100%. Neither the sequence of events nor the mechanisms involved in estrogen carcinogenesis in this model have been established. Results presented here indicate that estrogen induces renal tubular damage in the hamster kidney that is progressive and cumulative. Tubular injury was evident both as abnormal or lost microvilli, accumulation of cytoplasmic lipid droplets, vacuolization, and increases in secondary and tertiary lysosomes after 1.5 months of diethylstilbestrol (DES) treatment. Increasing tubular damage was evidence by the detachment of tubular cells, cell debris, and occluded renal tubular lumens. In an effort to repair proximal tubular damage in the hamster kidney elicited by estrogens, a 4.0-fold increase in proximal tubule BrdU labeling was evident at 4 months of DES or 17 beta-estradiol (E2) treatment and in earlier estrogen treatment periods (1-3 months). During this period, there was a significant increase in aneuploid cells in the hamster kidney, the near diploid frequency increased more than 6.0-fold, and the near tetraploid frequency increased at least 3.0-fold between 1.5 and 3.5 months of estrogen treatment. Based on these data, the early sequence of events leading to estrogen-induced renal neoplastic transformation in the hamster is presented.